Tobacco cessation pharmacotherapy use among racial/ethnic minorities in the United States: Considerations for primary care. Issue 3 (1st October 2017) - Hooper, Monica Webb; Payne, Michael; Parkinson, Kimberly A.
Abstract : Pharmacotherapies for tobacco cessation are efficacious and recommended during quit attempts. Racial/ethnic minorities in the United States are less likely to use medication-based aids for tobacco cessation, despite greater difficulty achieving long-term abstinence. The reasons for this include, among others, provider- and patient-level considerations. Primary care clinicians play an important role in encouraging racial/ethnic minority tobacco users to use cessation pharmacotherapy. To better understand pharmacotherapy use, we conducted a narrative review of patient-level factors that may determine uptake and adherence. This review indicates that social and cultural factors impact pharmacotherapy use, including health care experiences, beliefs, perceptions, and norms. The proportion of individuals using pharmacotherapy during quit attempts and adhering to the full course of treatment may be enhanced with greater attention to the ethnocultural concerns of these groups. Culturally appropriate assessment and brief advice delivered by primary care providers could yield significant benefits in population health. Recommendations for treating racial/ethnic tobacco users with pharmacotherapy for cessation are offered.